2002
DOI: 10.1038/sj.bjc.6600450
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of long-term outcome following high-dose chemotherapy in high-risk primary breast cancer

Abstract: We report on a predictive model of long-term outcome in 114 high-risk breast cancer patients treated with high-dose chemotherapy between 1989 and 1994. Paraffin-blocks from 90 of the 114 primaries were assessed for the presence of five risk factors: grade, mitotic index, protein expression of p53, HER2/neu, and oestrogen/progesterone receptor status; we could analyse the effect of risk factors in 84 of these 90 tumours. Seven-year relapse-free and overall survival was 58% (95% confidence interval 44 -74%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 30 publications
2
9
1
Order By: Relevance
“…The result of the prognostic effect of p53 seems to be in contradiction to results in the literature, where usually either no prognostic effect of p53 is reported (8) or patients with p53-positive tumors show a worse prognosis than patients with p53-negative tumors (16,28). An explanation for this result may be the scoring of p53 positivity in our study.…”
Section: Resultscontrasting
confidence: 93%
“…The result of the prognostic effect of p53 seems to be in contradiction to results in the literature, where usually either no prognostic effect of p53 is reported (8) or patients with p53-positive tumors show a worse prognosis than patients with p53-negative tumors (16,28). An explanation for this result may be the scoring of p53 positivity in our study.…”
Section: Resultscontrasting
confidence: 93%
“…Our data are consistent with previous long- term reports (13)(14)(15) and suggest that the activity of HDC in HRPBC is sustained over time.…”
Section: Discussionsupporting
confidence: 93%
“…Damon et al (14) reported 53% RFS and 65% OS rates at median FU of 6.9 years in 80 patients with Ն10 ϩ nodes treated with high-dose cyclophosphamide/ thiotepa/mitoxantrone. The actuarial 7-year RFS and OS rates of 114 HRPBC patients treated at City of Hope (Duarte, CA) with two different HDC regimens were 43% and 57%, respectively (15).…”
Section: Introductionmentioning
confidence: 99%
“…Factors that are present in ER -cells that enhance proliferation or inhibit apoptosis may favor replication competent viral vectors. Because ER -negativity may be associated with a poor prognosis following other forms of adjuvant therapy (30), oncolytic viral therapy holds promise in such a clinical setting.…”
Section: Discussionmentioning
confidence: 99%